Infestation and damage by Clavigralla tomentosicollis and Anoplocnemis curvipes (Hemiptera: Coreidae) in cowpea plants with modified leaf structure and pods in different positions relative to the canopy - Koona, P.; Osisanya, E.; Jackai, L.E.N.; Tonye, J. (Oxford University Press, 2004)
Potted cowpea, Vigna unguiculata (L.) Walp., plants were used to determine the effects of defoliation and pod position relative to the leaf canopy on infestation and damage by the coreid pod-bugs Clavigralla tomentosicollis Stål and Anoplocnemis curvipes (F.). Temperature measurements were taken within and outside the canopy to determine whether there was a correlation to seed damage. Seed damage decreased significantly with increasing defoliation in plants infested with C. tomentosicollis; an inverse trend was observed with A. curvipes. Temperatures within the canopy increased as the number of leaves decreased. As observed in the defoliation experiment, C. tomentosicollis and A. curvipes reacted differently in a free-choice situation between pods located outside or within the canopy. Significantly higher numbers of C. tomentosicollis concealed themselves within the canopy, where they caused more severe damage to seeds, in comparison with numbers and damage outside the canopy. These trends were reversed for A. curvipes. There was a significant negative correlation between percentage of seed damage and temperature with C. tomentosicollis, and a significant positive correlation with A. curvipes, both in defoliated plants and those with pods distributed outside and within the canopy. Overall, plants with less dense canopy, and long peduncles holding pods outside the canopy showed some resistance to C. tomentosicollis, which is the most damaging pod bug on cowpea. Because such cowpea plants harbor fewer C. tomentosicollis, they are likely to suffer less overall damage from infestation by the complex of pod bugs that occur concurrently in cowpea fields.